The Effectiveness of Acupressure and Warm Foot Soak Hydrotherapy on Increasing Muscle Strength and Range of Motion among Non-Hemorrhagic Stroke Patients - Mardiyono; Lalu Rian Setiawan Setiawan; Aris Santjaka (Alta Dharma Publisher, 2021)
The decreasing function of the upper and lower extremities is a frequent complication in non-hemorrhagic stroke patients who experience hemiparesis. The study aimed to analyze the effectiveness of acupressure, and warm foot soak hydrotherapy on increasing muscle strength and range of motion among non-hemorrhagic stroke patients. The Randomized control trial (RCT) was applied in this study. We select the samples using simple random sampling with 30 respondents. The data was analyzed using Paired t-test and an Independent t-test to determine the mean difference among the experimental and control groups. Independent t-test showed no significant difference p value >0.05 that the intervention and control groups were equally effective in increasing muscle strength and range of motion of the upper and lower extremities. However, the difference in the mean increase in muscle strength and range of motion in the intervention group was higher than in the control group. Acupressure with a warm foot soak hydrotherapy effectively increased muscle strength and range of motion of the upper extremities with the lower extremities in non-hemorrhagic post-stroke patients.